Juniperus excelsa M.Bieb; a medicinal plant with various pharmacological activities - Mohammad Mehdi Parvizi; Mohammad Mehdi Khazaii; Mahmoodreza Moein; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2018)
It is well accepted that medicinal plants are involved with numerous properties that may be considered for new drug discoveries. This review encompasses medicinal and pharmacological activities of Juniperus excelsa M.Bieb (Family: Cupressaceae) to draw a frame for further research. Considering the terms "Juniperus Excelsa" and "Pharmacological Activity", the databases Scopus, PubMed, Web of Science, and ScienceDirect were precisely searched up to early March of 2017 with the exception of agriculture and genetic-based science papers. Besides various ethnopharmacological properties, different parts of J. excelsa are shown to have distinct medicinal activities such as anti-microbial and anti-fungal, anti-parasite and anti leishmania, anti-oxidant and radical scavenging, cardiovascular, anti-diabetes, gastrointestinal, respiratory, wound healing, anti-angiogenic, immunomodulatory and antinociceptive, phytotoxic, cytotoxic activity, and therapeutic effect on cancer.